Serological evidence for the co‐circulation of two lineages of influenza D viruses in equine populations of the Midwest United States. (14th November 2017) - Nedland, H.; Wollman, J.; Sreenivasan, C.; Quast, M.; Singrey, A.; Fawcett, L.; Christopher‐Hennings, J.; Nelson, E.; Kaushik, R. S.; Wang, D.; Li, F.
Summary: Influenza D virus (IDV) is a newly described influenza type of the Orthomyxoviridae virus family that was first isolated from diseased swine in 2011 and has subsequently been detected in cattle around the world in 2014. In addition, serological evidence for IDV infection in humans has been recently established. Despite all the progress, the full range of susceptible hosts for this novel virus has yet to be determined, but includes swine, bovine, small ruminants and human. This study was designed to determine if equine is a possible host to this newly emerging influenza virus. Three hundred and sixty‐four equine serum samples were collected in 2015 from 141 farms within the Midwestern United States. Serum samples were examined using hemagglutination inhibition (HI) assay against two established IDV lineages (D/OK and D/660) and one IDV‐related human ICV lineage (C/JHB). Results of this study showed 44 (44 of 364, 12%) samples positive for antibodies against D/OK, 39 (39 of 364, 11%) samples positive for antibodies against D/660, and 41 (41 of 364, 11%) samples positive for antibodies against C/JHB. A subset of these samples was further confirmed via microtitre neutralization (MN) assay. Our data demonstrated that horses are susceptible to two lineages of IDV, and that these viruses were present in equine populations throughout multiple Midwestern states of the United States. These findings continue to support the need for further surveillance of IDV viruses in agricultural species to work towards a better understanding of the full host range and natural reservoirs of influenza D virus.